Research perspectives on English for academic purposes (Cambridge University Press, 2001)
The number of non-native students studying in English-medium universities has increased over the past decade. Paralleling this growth is the interest in English for Academic Purposes (EAP). No one research-based volume has yet investigated the theoretical issues and pedagogical concerns of the area. This wide-ranging volume of specially commissioned articles from leading scholars in the field aims to bring to the wider community current research in the field and its implications for pedagogy. It offers a state-of-the-art representation of research in EAP and will help define the field in the coming years.